Maps on annual and monthly surface water resources and coefficient of variation of annual runoff 1982 - Malaysia. Kementerian Pertanian. Bahagian Parit dan Taliair (Kuala Lumpur : Bahagian Parit dan Tali Air, Kementerian Pertanian, Malaysia, 1983)
PSZJBL